Norma Autentisitas dan Standar Buffer di TikTok : Tinjauan Analisis Wacana Kritis - Aprianus Paskalius Taboen (Pusat Riset dan Inovasi Nasional, 2024)
This study critically examines the construction and reproduction of authenticity norms and buffer standards in Indonesian TikTok users’ communication practices. Employing Norman Fairclough’s Critical Discourse Analysis (CDA) framework, the research explores how digital expressions—through captions, comments, and hashtags—reflect power relations, algorithmic logic, and social norms that operate subtly yet effectively. An analysis of five popular TikTok contents reveals that so-called “authentic” expression is not spontaneous honesty but rather a curated and performative construct aligned with algorithmic expectations and community aesthetics. The concept of the buffer standard refers to implicit symbolic boundaries that define which expressions are “acceptable” and which risk social or systemic rejection. The study concludes that freedom of expression in digital spaces like TikTok is always a product of negotiation between user agency, algorithmic pressure, cultural norms, and the commodification of identity.